2010
DOI: 10.1002/bjs.7087
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of single-incision laparoscopic cholecystectomy versus minilaparoscopic cholecystectomy

Abstract: SILC is superior to MLC in terms of cosmetic outcome, but not in postoperative pain and requirement for analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
171
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 19 publications
5
171
2
5
Order By: Relevance
“…A mere 2 to 3-mm incision is necessary using needlescopic devices, and the resulting scars are almost invisible. Only one randomized trial has compared needlescopic cholecystectomy with pure single-incision cholecystectomy, reporting a positive effect of the single -incision technique in terms of pain and cosmetic outcomes (19). However, that trial was not blinded.…”
Section: Discussionmentioning
confidence: 99%
“…A mere 2 to 3-mm incision is necessary using needlescopic devices, and the resulting scars are almost invisible. Only one randomized trial has compared needlescopic cholecystectomy with pure single-incision cholecystectomy, reporting a positive effect of the single -incision technique in terms of pain and cosmetic outcomes (19). However, that trial was not blinded.…”
Section: Discussionmentioning
confidence: 99%
“…Our figures suggest that though SILC has lower pain scores, there is no significant difference between the two groups. 12,13,[17][18][19] The final operative site scar at the umbilicus in SILC is cosmetically very acceptable, because after a month of surgery the scar is hardly seen. So is this an answer to scar less surgery?…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in postoperative pain between the two groups on post operative day 1. A randomized trial comparing SPLC with MPLC showed that SPLC and MPLC were similar in terms of postoperative pain and requirement for analgesia [13]. Another study comparing SPLC and MPLC showed that patients in the SPLC group experienced less postoperative pain than those in the MPLC group.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that patients in the SPLC group were more satisfied with their cosmetic results. A randomized trial comparing SPLC with MPLC showed that SPLC was superior to MPLC in terms of cosmesis [13]. Patient satisfaction scores were also higher in the SPLC group, thereby suggesting that patients in the SPLC group were more satisfied with the overall results of the procedure.…”
Section: Discussionmentioning
confidence: 99%